Pengaruh Milling Terhadap Laju Disolusi Campuran Metampiron-Fenilbutason (7:3) - Soewandhi, Sundani Nurono; Haryana, Aris (UI Scholars Hub, 2007)
In pharmaceutical process, milling is a common process to produce particle in certain expectation size. Impact of milling process could lead to physical interaction. Dissolution rate will change as an impact of physical interaction. To observe physical interaction between methampyrone and phenylbutazone during milling process, is needed to analyze its X-ray diffractogram, DSC thermogram and dissolution rate. Data of X-ray diffractogram, differential scanning calorimetry and dissolution test, showed that physical interaction occurred after 5,5 hours and 18 hours of milling and cause enhancement of dissolution rate of phenylbutazone. Dissolution rate of methampyrone was constant after 5,5 hours of milling. Decreasing dissolution rate of methampyrone occured after 18 hours of milling.